Investigating geohazard risk in mountainous areas for underground gas storage using InSAR and development of a protocol for hazard prevention - Siluo Lei; Jiawen Chen; Tingjun Wen; Elton J. Chen; Jiangen Xu; Ji Gao; Luyi W. Shen (PLoS ONE, 2025)
XiangGuoSi reservoir is a depleted gas reservoir that has recently (in 2014) been converted to an underground gas storage facility. It stores gas in the reservoir during the summer season and produces gas in the winter season. In this work, we present a case report on using InSAR to monitor the mountainous area beneath where the XiangGuoSi gas reservoir is located, along with its supporting pipeline infrastructures. Data, containing 159 scenes, from C-band Synthetic Aperture Radar (SAR) aboard Sentinel-1 satellite is used here, the processing period covered a timespan of 5.6 years. Importantly, we find that the surface deformation is not correlated with the reservoir’s gas injection/extraction history. This indicates that the gas storage’s underground operation does not increase geohazard risk in the area. Further, this indicates the reservoir rock’s pore structure is rather stable even during the cycles of injection/extraction, suggesting a stable reservoir performance even into the far future. Nevertheless, the natural movement of the mountain still poses a landslide risk for the pipeline structure. Given our observed deformation is mostly monotonically downward (subsidence) and in many points, linear, we develop a protocol using 1. the local maximum deformation rate point’s proximity to the pipeline and 2. the rate and total deformation magnitude reported during the monitoring period. After all, this report shows the capability of InSAR as a tool for mapping geohazards for mountainous areas where critical infrastructures are in the vicinity.